ECOLIMBAH : Cross-Ecosystem Pollution Reduction through Creative Craft Business with Commercial Value - Rahmaningtyas, Wisudani; Widhiastuti, Ratieh; Pramusinto, Hengky; Purasani, Hana Netti; Ramadhani5, Putri Della (Jurnal Pengabdian UNDIKMA, 2023)
This community service program aims to provide knowledge and skills to the community on how to manage and process household waste, especially plastic, into valuable and marketable products. The methods for implementing community service activities included lectures, practical exercises, and guidance. The evaluation used in the community service activities involved the utilization of questionnaires and their subsequent qualitative descriptive analysis. The outcome of the community service activities was an increase in knowledge about waste bank management and skills in utilizing plastic waste to create woven plastic bags for water bottle holders. In conclusion, community service has proven to be a highly effective endeavor, providing valuable knowledge and skills to the partners while promoting environmental awareness and sustainability through plastic crochet.